Measurement of kidney perfusion by magnetic resonance imaging: comparison of MRI with arterial spin labeling to para-aminohippuric acid plasma clearance in male subjects with metabolic syndrome - Ritt, Martin; Janka, Rolf; Schneider, Markus P.; Martirosian, Petros; Hornegger, Joachim; Bautz, Werner; Uder, Michael; Schmieder, Roland E. (Nephrology, dialysis, transplantation, 2010)
Background. Magnetic resonance imaging with arterial spin labeling (MRI–ASL) is a non-invasive approach to measure organ perfusion. We aimed to examine whether MRI–ASL kidney perfusion measurements are related to measurements of renal plasma flow (RPF) by para-aminohippuric acid (PAH) plasma clearance and whether changes of kidney perfusion in response to treatment with telmisartan can be detected by MRI–ASL. Methods. Twenty-four patients with metabolic syndrome and an estimated creatinine clearance according to Cockroft and Gault of ≥60 ml/min were included in the study. Kidney perfusion was assessed by MRI–ASL measurements of a single coronal kidney slice (with flow-sensitive alternating inversion recovery and true fast imaging with steady-state processing sequence) and by measurements of RPF using PAH plasma clearance before and after 2 weeks of treatment with the angiotensin receptor blocker telmisartan. All MRI–ASL examinations were performed on a 1.5 T scanner. Results. Two weeks of therapy with telmisartan led to a significant increase of RPF (from 313 ± 47 to 348 ± 69 ml/min/m, P = 0.007) and MRI–ASL kidney perfusion measurements (from 253 ± 20 to 268 ± 25 ml/min/100 g, P = 0.020). RPF measurements were related with MRI–ASL kidney perfusion measurements (r = 0.575, P < 0.001). Changes of RPF measurements and changes of MRI–ASL kidney perfusion measurements in response to treatment with telmisartan revealed a close relationship when expressed in absolute terms (r = 0.548, P = 0.015) and in percentage changes (r = 0.514, P = 0.025). Conclusions. Perfusion measurement of a single coronal kidney slice by MRI–ASL is able to approximate kidney perfusion and to approximate changes in kidney perfusion due to pharmacological intervention.